State Authority and Public Interest: Reinterpreting Age Restriction Policy through the Doctrine of Tassaruf al-imam bi al-Maslahah - Rajni, Dinda Kusuma; Nafisah, Izza Zahrotun; Hardi, Frilia Shafitri (Suhuf: International Journal of Islamic Studies, 2026)
Background: This study examines the facultative age restriction model for digital platform users under Government Regulation Number 17 of 2025 (PP Tunas) within Indonesia’s socio-digital context. The regulation adopts a parental consent–based framework inspired by the GDPR, positioning parents as primary decision-makers in children’s digital access. Objective: This research aims to evaluate the effectiveness of this model and its compatibility with Indonesia’s socio-digital conditions through the Islamic legal principle of Tasarruf al-Imam ʿala al-Raʿiyyah Manutun bi al-Maslahah. Method: This study employs a normative legal method using statutory, conceptual, comparative, and case approaches to assess the delegation of child protection responsibilities to parents. Result: The findings indicate that low parental digital literacy, unequal access to digital infrastructure, and socio economic disparities significantly weaken the implementation of the model, undermining effective child protection and rendering it socially ineffective despite its formal validity. Conclusion: The parental consent–based model is inadequate to ensure optimal child protection in Indonesia’s current context. This study proposes a reconstruction toward a more restrictive, state-imposed age regulatory model grounded in maqasid al-shari‘ah, particularly the protection of lineage hifz al-nasl and intellect hifz al-‘aql, to better align legal norms with socio-economic realities.